Descriptive analysis of the national drug adverse events (AEs) database in Lebanon - Rita Karam; Sarah Reda El Sayed; Aya Ibrahim; Joya-Maria Karam; Souheil Hallit; Abeer Zeitoun (Journal of Pharmaceutical Policy and Practice)
Background Adverse Events (AE) including both Adverse Drug Reactions (ADRs) and Medication Errors (MEs) are worldwide health issues tackled by Pharmacovigilance (PV) systems. In Lebanon, ADRs and MEs are monitored by the Lebanese National Pharmacovigilance Program (LNPVP) implemented under the supervision of the Lebanese Ministry of Public Health (MoPH) to ensure the post-marketing surveillance of each authorised medication. The objective of this paper is to evaluate the prevalence of detected AEs within the Lebanese population in a descriptive analysis.Methods This is a retrospective analysis-based study that describes collected national AE cases for all marketed medications as well as medications in the pre-marketed phase as part of clinical studies in Lebanon, the LNPVP data system spontaneously received that from Marketing Authorisation Holders (MAHs) between 2018 and 2023.Results Since the initiation of the LNPVP programme, a total of 21,631 Individual Case Safety Reports (ICSRs) have been processed; 3,855 of which were excluded and the remaining 17,776 ICSRs are the subject of this paper and correspond to 37,768 AEs associated with medications authorised for use in Lebanon. Among respondents, 55.3% were females, whereas 37.9% were associated with males. In addition, the LNPVP has received a total of 1,961 cases of suspected medication errors, constituting 5.2% of the overall reported AEs.Conclusion Our results showed that Lebanon, a country that suffers from a turbulent economic and health context, was able to implement a PV system and operate with efficiency while evaluating a 5-year worth of ICSR reports. The dissemination of this information promotes stakeholder awareness by encouraging a collaborative approach among patients, healthcare providers, and regulatory authorities in Lebanon. However, further research is warranted to investigate factors contributing to MEs in Lebanon.